Setting the Agenda: Exploring Florida Residents' Perceptions of Water Quality and Quantity Issues - Arthur Leal; Joy N. Rumble; Alexa J. Lamm (Journal of Applied Communications, 2015)
Water quantity and quality are among the top issues currently facing Florida. To understand residents’ perceptions of these issues as well as understand how agenda-setting may be used to influence residents’ behaviors and opinions surrounding water issues, this study explored Florida residents’ opinions of water. Agenda-setting served as the conceptual framework to aid in understanding where water quality and quantity emerge on the public’s agenda. Responses were obtained from 469 Florida residents via an online survey. The results showed respondents believed water quality had not changed, with the exception of the quality of bays, which they believed was getting worse. Water quality was found to be an issue of high importance among respondents, especially in regard to the quality of drinking water. Respondents believed water quantity was highly important; however, more importance was associated with water quality issues. The results of this study identified the current disconnect that exists among residents concerning water issues. This study also established the salience of water issues on the public’s agenda and how Florida residents could be better informed. A statewide communication campaign focused on both water quality and quantity issues was recommended to decrease the disconnect that currently exists between residents’ perceptions and the reality of water issues. This campaign should utilize the technology-based outlets to stay informed with the public’s agenda to personalize communication efforts. These efforts would increase the public’s interest concerning water issues by reducing redundant information and diluting important issues.
Keywords: Water; quality; quantity; agenda-setting; public opinion